Dispersal of thermophilic beetles across the intercontinental Arctic forest belt during the early Eocene. Issue 1 (December 2017) - Brunke, Adam; Chatzimanolis, Stylianos; Metscher, Brian; Wolf-Schwenninger, Karin; Solodovnikov, Alexey
Abstract Massive biotic change occurred during the Eocene as the climate shifted from warm and equable to seasonal and latitudinally stratified. Mild winter temperatures across Arctic intercontinental land bridges permitted dispersal of frost-intolerant groups until the Eocene-Oligocene boundary, while trans-Arctic dispersal in thermophilic groups may have been limited to the early Eocene, especially during short-lived hyperthermals. Some of these lineages are now disjunct between continents of the northern hemisphere. Although Eocene climate change may have been one of the most important drivers of these ancient patterns in modern animal and plant distributions, its particular events are rarely implicated or correlated with group-specific climatic requirements. Here we explored the climatic and geological drivers of a particularly striking Neotropical-Oriental disjunct distribution in the rove beetleBolitogyrus, a suspected Eocene relict. We integrated evidence from Eocene fossils, distributional and climate data, paleoclimate, paleogeography, and phylogenetic divergence dating to show that intercontinental dispersal ofBolitogyrus ceased in the early Eocene, consistent with the termination of conditions required by thermophilic lineages. These results provide new insight into the poorly known and short-lived Arctic forest community of the Early Eocene and its surviving lineages.